The effect of electoral institutions on party membership in central and east Europe - Smith, A; Dr Alison F Smith (2013)
Party membership levels in the new democracies of central and east European were predicted to remain universally low, stymied by post-communist legacies, the availability of state funding and the prevalence of mass media communications (van Biezen, 2003; Kopecký, 2007). However, more than two decades after the fall of the Berlin Wall, membership levels vary considerably between countries, and also between individual parties within party systems. Using freshly gathered party membership data, elite surveys and interviews, this thesis explores a number of institutional hypotheses to test whether, as in western democracies, electoral institutions influence how parties organise and campaign. This thesis finds that national electoral systems, municipal electoral rules and business funding regulations have an observable impact on how parties use their members. In particular, 'decentralised' electoral systems encourage greater involvement of members in voter contacting and other small campaign tasks. This thesis concludes that, contrary to the dominant literature, the availability of state funding has little impact on party membership recruitment. Instead, central and east European parties' attitudes to members are shaped by a complex interaction of institutional, cultural, ideological and strategic factors.